Comparison of SynCAM1/CADM1 PDZ interactions with MUPP1 using mammalian and bacterial pull‐down systems - Martina Baliova; Frantisek Jursky (Brain and Behavior, 2020)
Abstract Background Synaptic cell adhesion molecule 1 (SynCAM1) also known as cell adhesion molecule 1 (CADM1) is a transmembrane cell adhesion protein that operates in a variety of physiological and pathological cellular contexts, and its interaction with the PDZ signalling protein MUPP1 have been previously implicated in autism spectrum disorder (ASD). Methods We used in vitro pull‐down systems based on the bacterial and mammalian extracts to study SynCAM1/CADM1 PDZ interactions with MUPP1 at various conditions. Results So far, the investigated interaction of SynCAM1/CADM1 with MUPP1 has been mostly attributed to an unspecified region of MUPP1 PDZ domains 1–5 or exclusively to domain 2, using a yeast two‐hybrid system. We also confirmed the single interaction of native synaptosomal CADM1 with PDZ domain 2. However, in this work, using recombinant proteins overexpressed in bacteria, we found an in vitro pull‐down conditions in which all first five domains and, to a much lesser extent, MUPP1 domains 7 and 11 significantly interacted with the whole C‐terminal domain of SynCAM1/CADM1. These PDZ interactions were confirmed by a pull‐down assay using the last seven amino acids of the SynCAM1/CADM1 PDZ motif and using two fusion partners. Multiple interactions were additionally replicated using the continuous N‐terminal MUPP1 protein fragment, which included first five PDZ domains, containing either intact or mutated domain 2. Conclusions We hypothesize that multiple interactions might exist in vivo, representing transient low‐affinity interactions or alternative binding sites on MUPP1 when domain 2 is occupied or occluded by the interaction with other ligands. This newly identified interactions extend the potential genetic mutations, possibly affecting SynCAM1/CADM1/MUPP1 function. Possible reasons for the absence of some of the identified CADM1 PDZ interactions in mammalian extracts are discussed.